2012
DOI: 10.1254/jphs.11r08fm
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Approaches to the Treatment, Prophylaxis, and Diagnosis of Alzheimer’s Disease: Novel PET/SPECT Imaging Probes for Diagnosis of Alzheimer’s Disease

Abstract: Abstract. Alzheimer's disease (AD) is a neurodegenerative disease of the brain associated with irreversible cognitive decline, memory impairment, and behavioral changes. Postmortem brains of AD patients reveal neuropathologic features, in particular the presence of senile plaques (SPs) and neurofibrillary tangles (NFTs), which contain β-amyloid peptides and highly phosphorylated tau proteins. Currently, AD can only be definitively confirmed by postmortem histopathologic examination of SPs and NFTs in the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…Further investigation is required to confirm the usefulness of those scores for the prediction of the conversion from MCI to AD in Japanese MCI patients. The compatibility of our diagnostic criteria for MCI with those used in other studies should be confirmed by pathologically confirmed markers, such as the decline of β-amyloid levels in cerebrospinal fluid, or elevation of brain β-amyloid deposition, which recently has come to be detectable by positron emission tomography [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is required to confirm the usefulness of those scores for the prediction of the conversion from MCI to AD in Japanese MCI patients. The compatibility of our diagnostic criteria for MCI with those used in other studies should be confirmed by pathologically confirmed markers, such as the decline of β-amyloid levels in cerebrospinal fluid, or elevation of brain β-amyloid deposition, which recently has come to be detectable by positron emission tomography [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Aβ clearance from the brain as early as possible could be a primary target for therapeutic strategies in AD. For this purpose, the development of a method for early and precise diagnosis would be the most important step (56). In contrast, by the elucidation of the interaction between pathologies, novel targets for the diagnosis may be found, and the developmental opportunities and possibilities could be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we designed molecular probes for nuclear medicinal imaging the distribution of aggregates of Aβ and hyperphosphorylated tau protein in the brain of a patient with AD, which satisfied the following requirements: 1) high blood-brain barrier permeability; 2) high and specific binding ability to Aβ and tau aggregates; and 3) rapid elimination from normal regions of the brain. Consequently, we succeeded in developing 18 F-labeled pyridyl benzofuran derivative, 18 F-FPYBF-2, as a probe for PET imaging of Aβ plaques [28][29][30][31][32][33][34][35][36] and 123 I-labeled benzo imidazopyridine (BIP) derivative, BIP-3, as a probe for SPECT imaging of tau aggregates [37][38][39][40][41] (Fig. 3).…”
Section: Molecular Imaging Of β-Amyloid Plaques and Taumentioning
confidence: 99%